Effects of gasification temperature and atmosphere on char structural evolution and AAEM retention during the gasification of Loy Yang brown coal - Li, T.; Zhang, L.; Dong, Li; Zhang, S.; Qiu, P.; Wang, S.; Li, Chun-Zhu (Elsevier, 2017)
© 2017 Elsevier B.V.This study aims to investigate the influence of gasification temperature on the evolution of char structure and the retention of alkali and alkaline earth metallic (AAEM) species for a Victorian brown coal. The experiments were carried out at 800, 850 and 900 °C in pure CO2, 15% H2O balanced with Ar and 15% H2O balanced with CO2 in a one-stage fluidised-bed/fixed-bed reactor. FT-Raman spectroscopy was used to characterise the structural features of the chars obtained at varying conversion levels during gasification. The concentrations of AAEM species in the chars left after gasification were quantified with inductively coupled plasma – optical emission spectroscopy. The specific char-O2 reactivity of the gasified char was measured in a thermogravimetric analyser. The results show that the CO2 and H2O partly compete for the active sites on the char. The increasing total Raman area caused by the formation of O-containing structures in char does not appear to be the only factor determining the char gasification rate in H2O-containing atmospheres. With increasing temperature, CO2 plays an increasingly more important role in the char evolution and subsequently influences the AAEM retention in char from the gas mixture. The gasification temperature does not change the individual reaction pathway for char-CO2 or char-H2O reaction within temperature range investigated.